Lignin-Based/Polypyrrole Carbon Nanofiber Electrode With Enhanced Electrochemical Properties by Electrospun Method - Hu, Zhou-Rui; Li, Dan-Dan; Kim, Tae-Hee; Kim, Min-Seok; Xu, Ting; Ma, Ming-Guo; Choi, Sun-Eun; Si, Chuanling (Frontiers in Chemistry, 2022)
Tailoring the structure and properties of lignin is an important step toward electrochemical applications. In this study, lignin/polypyrrole (PPy) composite electrode films with microporous and mesoporous structures were designed effectively by electrostatic spinning, carbonization, and in situ polymerization methods. The lignin can not only reduce the cost of carbon fiber but also increase the specific surface area of composite films due to the removal of carbonyl and phenolic functional groups of lignin during carbonization. Besides, the compact three-dimensional (3D) conductive network structures were constructed with PPy particles densely coated on the lignin nanofibers, which was helpful to improve the conductivity and fast electron transfer during the charging and discharging processes. The synthesized lignin carbon fibers/PPy anode materials had good electrochemical performance in 1 M H2SO4 electrolyte. The results showed that, at a current density of 1 A g−1, the lignin carbon nanofibers/PPy (LCNFs/PPy) had a larger specific capacitance of 213.7 F g−1 than carbon nanofibers (CNFs), lignin carbon nanofibers (LCNFs), and lignin/PPy fiber (LPAN/PPy). In addition, the specific surface area of LCNFs/PPy reached 872.60 m2 g−1 and the average pore size decreased to 2.50 nm after being coated by PPy. Therefore, the independent non-binder and self-supporting conductive film is expected to be a promising electrode material for supercapacitors with high performance.